Sendo
, logo P(5) é igual a:
a) 0
b) 2
c) 4
d) 6
Soluções para a tarefa
Respondido por
21
Tome
então tem-se
6![P(6-1)= P(5)= 6^{2} -7\times6 +10 = 36-42+10 = 4 P(6-1)= P(5)= 6^{2} -7\times6 +10 = 36-42+10 = 4](https://tex.z-dn.net/?f=P%286-1%29%3D+P%285%29%3D++6%5E%7B2%7D+-7%5Ctimes6+%2B10+%3D+36-42%2B10+%3D+4)
Portanto a resposta é a letra C.
6
Portanto a resposta é a letra C.
Perguntas interessantes
Inglês,
11 meses atrás
Português,
11 meses atrás
Matemática,
11 meses atrás
Inglês,
1 ano atrás
Português,
1 ano atrás
Pedagogia,
1 ano atrás
Matemática,
1 ano atrás